Pemanfaatan key opinion leader dalam strategi digital PR BNNP Jawa Timur - Chintya Ihzabella; Dian Hutami Rahmawati (Universitas Garut, 2026)
Abstract This study examines the digital public relations strategy implemented by the National Narcotics Agency of East Java Province in utilizing Key Opinion Leaders (KOLs) to support public communication. The institution is responsible for implementing programs aimed at preventing and combating drug abuse and illicit drug trafficking. However, it faces challenges related to public communication that tends to be formal and one-way, which limits its ability to build emotional connections with the public and encourage greater community engagement.This research employs a descriptive qualitative approach to understand the communication processes and strategies carried out by the institution. Data were collected through in-depth interviews with key informants involved in the communication strategy and through direct observation of communication activities conducted by the agency.The findings indicate that the digital public relations strategy is implemented systematically based on the stages of The ROSTIR Model. The initial stage involves identifying public communication needs by monitoring mass media coverage and reviewing public complaint channels. The next stage focuses on determining communication objectives, including expanding audience reach and increasing public engagement. Strategic planning is carried out by determining the characteristics of suitable Key Opinion Leaders, designing the selection mechanism, and developing communication messages. Tactical implementation is conducted through content competitions, collaboration programs with KOLs, strengthening internal capacity, and integrating various communication media. The final stage involves evaluation using performance indicators to assess the effectiveness of the strategy and to provide a basis for improving future communication strategies. Keywords: Digital public relations;key opinion leader; public communication; bnnp east java, communication strategy. Abstrak Penelitian ini menganalisis strategi digital public relations yang diterapkan oleh Badan Narkotika Nasional Provinsi Jawa Timur dalam memanfaatkan Key Opinion Leaders (KOL) untuk mendukung komunikasi publik. Lembaga tersebut memiliki tanggung jawab dalam melaksanakan program pencegahan dan pemberantasan penyalahgunaan serta peredaran gelap narkoba. Namun, dalam pelaksanaannya masih terdapat tantangan berupa pola komunikasi publik yang cenderung formal dan bersifat satu arah, sehingga belum sepenuhnya mampu membangun kedekatan emosional dengan masyarakat dan meningkatkan keterlibatan publik. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk memahami proses dan strategi komunikasi yang dilakukan. Pengumpulan data dilakukan melalui wawancara mendalam dengan informan yang terlibat dalam pelaksanaan strategi komunikasi serta observasi langsung terhadap aktivitas komunikasi yang dijalankan oleh lembaga tersebut. Hasil penelitian menunjukkan bahwa strategi digital public relations dijalankan secara sistematis dengan mengacu pada tahapan dalam The ROSTIR Model. Tahap awal dilakukan melalui identifikasi kebutuhan komunikasi publik dengan memantau pemberitaan media massa serta menelaah laporan atau pengaduan masyarakat. Selanjutnya, organisasi menetapkan tujuan komunikasi yang berfokus pada perluasan jangkauan audiens serta peningkatan keterlibatan masyarakat. Tahap perencanaan meliputi penentuan karakteristik Key Opinion Leaders, penyusunan mekanisme pemilihan, serta perancangan pesan komunikasi yang relevan. Implementasi strategi dilakukan melalui kompetisi konten, program kolaborasi dengan KOL, penguatan kapasitas internal, serta integrasi berbagai saluran media komunikasi. Tahap evaluasi dilakukan dengan menggunakan indikator kinerja untuk menilai efektivitas strategi sekaligus menjadi dasar penyempurnaan strategi komunikasi di masa mendatang. Kata-kata kunci: Digital public relations; key opinion leader; komunikasi publik; bnnp jawa timur; strategi komunikasi.